Identifying the best combination of vegetation and paving materials to improve the outdoor thermal comfort in a campus courtyard - Zihao Ye; Jing Liu; Zhihuan Huang (Scientific Reports)
Abstract The urban heat island effect poses significant challenges to urban residents by diminishing thermal comfort and altering outdoor behaviors in hot environments. Although improvements in green space and adjustments to paving materials can alleviate these impacts, their combined effects remain insufficiently studied. This study employed ENVI-met software to simulate nine vegetation-paving material combinations and assess their influence on the thermal environment and thermal comfort of a campus courtyard during summer. Regression analyses were conducted to explore the interactions among these strategies. Air temperature (T a ), surface temperature (T s ), relative humidity (RH) and physiological equivalent temperature (PET) were used as key indicators to evaluate the effectiveness of each scenario. Results showed that “trees + lawn” and “trees + shrubs + lawn” were most effective in reducing T a , T s and PET, while increasing RH. In contrast, the “lawn + shrubs” configuration demonstrated limited effectiveness. Among the paving materials, high-reflectivity concrete yielded the greatest reductions in T a and T s , followed by standard concrete, with asphalt being the least effective. However, high-reflective concrete also led to an increase in PET due to increased radiant heat exposure. These findings provide a valuable foundation for informing microclimate-responsive landscape strategies in campus courtyards under summer conditions.